Case report: Endovascular coil embolization of an aneurysm at the origin of the accessory middle cerebral artery from the A1 segment as the collateral artery to twigs - Zhang, Lei; Su, Han; Yu, Jinlu (Frontiers in Neurology, 2023)
An aneurysm at the origin of the accessory middle cerebral artery (AccMCA) from the A1 segment of the anterior cerebral artery (ACA) as the supplying artery of a twig-like MCA is exceptional. In this study, we reported on such a case and presented a review of the relevant literature. A 56-year-old male suffered a subarachnoid hemorrhage. Digital subtraction angiography confirmed a twig-like MCA and a ruptured aneurysm at the origin of the AccMCA. Endovascular coil embolization of the aneurysm was performed. After the microcatheter was positioned in the aneurysm, soft coils were delivered to complete the embolization. Postoperatively, the patient recovered uneventfully. One month later, the patient returned to his job without any neurological deficits. Postoperative computed tomography at the 3-month follow-up showed that the brain tissue was normal. By reporting our case and reviewing the relevant literature, we found that endovascular coil embolization for such aneurysms at the AccMCA origin is feasible in certain cases.